Menstrual health and school absenteeism among adolescent girls in Uganda (MENISCUS): a feasibility study - Miiro, George; Rutakumwa, Rwamahe; Nakiyingi-Miiro, Jessica; Nakuya, Kevin; Musoke, Saidat; Namakula, Juliet; Francis, Suzanna; Torondel, Belen; Gibson, Lorna J.; Ross, David A.; Weiss, Helen A. (BMC women's health, 2018)
Management of menstruation can present substantial challenges to girls in low-income settings. In preparation for a menstrual hygiene intervention to reduce school absenteeism in Uganda, this study aimed to investigate menstruation management practices, barriers and facilitators, and the influence of menstruation on school absenteeism among secondary school students in a peri-urban district of Uganda. Qualitative and quantitative studies were conducted among consenting girls and boys aged 14-17 years in four secondary schools in Entebbe sub-District, Uganda. Methods included group and in-depth interviews with students, a quantitative cross-sectional questionnaire, a prospectively self-completed menstrual diary, key informant interviews with policy makers, and observations of school water, sanitation and hygiene facilities. Multiple logistic regression was used to assess factors associated with school absenteeism during the most recent menstrual period. Girls reported substantial embarrassment and fear of teasing related to menstruation in the qualitative interviews, and said that this, together with menstrual pain and lack of effective materials for menstrual hygiene management, led to school absenteeism. All policy makers interviewed reported poverty and menstruation as the key factors associated with school attendance. The 352 girls with questionnaire data had a median age of 16 (inter-quartile range (IQR) = 15,16) years, with median age at menarche of 13 (IQR = 13,14) years. Of these, 64 girls (18.7%) reported having stained their clothes and 69 (19.7%) reported missing at least 1 day of school, during their most recent period. Missing school during the most recent period was associated with physical symptoms (headache (odds ratio (OR) = 2.15, 95%CI:1.20, 3.86), stomach pain (OR = 1.89, 95%CI:0.89, 4.04), back pain (OR = 1.75, 95%CI:0.97, 3.14), and with changing protection 4 or more times per 24 h period (OR = 2.08, 95%CI:1.06, 4.10). In the diary sub-study among 40 girls, school absence was reported on 28% of period-days, compared with 7% of non-period days (adjusted odds ratio = 5.99, 95%CI:4.4, 8.2; p < 0.001). In this peri-urban Ugandan population, menstruation was strongly associated with school attendance. Evaluation of a menstrual management intervention that address both psychosocial (e.g. self-confidence, attitudes) and physical (e.g. management of pain, use of adequate menstrual hygiene materials, improved water and sanitation facilities) aspects of menstruation are needed.